Study on the Bond Strength of Steel-Concrete Composite Rectangular Fluted Sections - Surya J. Varma; Jane H. Henderson (Advances in Civil Engineering)
Concrete-filled steel tube (CFST) sections are structural members that effectively use the best properties of steel and concrete. Steel tube at the outer perimeter effectively resists tension and bending moments and also increases the stiffness of the section as steel has a high modulus of elasticity. The infilled concrete delays the local buckling of the thin outer steel tube. The interface bond strength plays a major role in the composite action of CFST sections. Provision of rectangular flutes on steel tube on CFST sections will improve the bond failure load and thereby the performance of CFST sections significantly. In this paper, the bond strength and displacement characteristics of steel-concrete composite sections are determined by incorporating rectangular shaped flutes into the steel tube. A total of five sections were tested to assess the influence of flutes on the bond strength. These tested sections are analyzed and are used to develop a finite element model using the finite element software ABAQUS version 6.13. The parameters chosen for the FE study are (i) type of flutes (outward and inward), (ii) D/t ratio (40, 60, and 80), (iii) number of flutes (2, 3, 4, 5, and 6), and (iv) dimension of flutes ((20 mm × 10 mm), (40 mm × 10 mm), and (60 mm × 10 mm)). Bond failure load is found to be higher for outward fluted sections compared to inward fluted and plain CFST sections.